Mineral Zeolite: Penyelamat Tanah, Air, dan Udara - H. Zulkarnain Muin (Jurnal Zeolit Indonesia, 2005)
God has given us rain / water as a mercy gift. Why, we are human being make it become a disaster? Why our efforts to overcome floods, pollutions until now, did not give good results yet? Because, the most precious gift has been given by God, free! And often, we can not appreciate something got free. That's why, we are used, on purpose, to flow the rain water to drainage, small / big river and last, to the sea/ ocean. Natural Zeolites, which are treated physically & chemically (TNZ) can be used succesfully, as media water filter and gas / air (adsorbent) purifier. A certain type of TNZ can neutralize the acid rain and make its void (channel) pores as prisoner for the heavy dangerous metals. If we install the pipe of factory ehimney horizontally (not vertically) and insert the ZA granules in the muffler that way, then we will make our air, fresh and clean. Grey Water which come out from the domestic waste water, will be changed into clear (transparant) clean water, if filtered through TNZ filter bed, while Biolite will change the black water into excellent organic Fertilizer. Biolite is a liquid product, produced from Zeolite powder and probiotic bacterie & additives. The Zeolite powder will adsorb the colour & bad smells and the bacterie will reduce the faeces volume of the Black Water. By using a new (innovative) Domestic Waste Water Treatment Plant (DWWTP) you can easily recycle and reuse the final effluent. Beside this DWWTP will give you excellent organic fertilizer as added value, the investment & operational costs are much reduced & efficient compare to the old (conventional) one. So, you can rely on Zeolite minerals (TNZ, ZA) & its derivat Biolite, not only as soil conditioner, but also to make you sure, that your plants will grow fertile. It is our duty to maintain this Earth, as God create it in a prosperous & equilibrium status.